An effective way to increase the high-frequency permeability of Fe3O4 nanorods. Issue 26 (15th June 2016) - Ren, Xiao; Yang, Haitao; Tang, Jin; Li, Zi-An; Su, Yi kun; Geng, Sai; Zhou, Jun; Zhang, Xiangqun; Cheng, Zhaohua
Abstract : The oriented Fe3 O4 magnetic nanorods (NRs) were successfully synthesized with a high-frequecy permeability. Abstract : Uniform Fe3 O4 magnetic nanorods (NRs) were successfully synthesized and oriented in epoxy resin under a rotating magnetic field. Magnetic induction fields within and around a single Fe3 O4 nanorod in the remanence state were obtained by off-axis electron holography. The induction fields indicated a single domain state of the highly anisotropic Fe3 O4 nanorod due to its strong magnetic shape anisotropy. Quantitative magnetic moment analysis of the obtained phase image yielded an average magnetization of 0.53 T of a single Fe3 O4 nanorod. Moreover, the real part of the permeability ( μ ′) of magnetic-oriented Fe3 O4 NRs is obviously higher than that of random Fe3 O4 NRs in the GHz range. The oriented Fe3 O4 NRs exhibit a higher resonance peak at 4.75 GHz compared to the bulk counterpart (1.2 GHz) in the frequency dependence of μ in the range of 1–10 GHz. Moreover, the calculated μ value of the oriented Fe3 O4 NRs could be improved to 4.22 with the increased dipolar interaction strength using the OOMMF software. These results could play a guiding significance in the development of an effective method to improve the permeability of magnetic nanomaterials at GHz working frequency.